The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.yrtph.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Tobacco Heating System 2.2. Part 2: Chemical composition, genotoxicity, cytotoxicity, and physical properties of the aerosol

Abstract: The chemical composition, in vitro genotoxicity, and cytotoxicity of the mainstream aerosol from the Tobacco Heating System 2.2 (THS2.2) were compared with those of the mainstream smoke from the 3R4F reference cigarette. In contrast to the 3R4F, the tobacco plug in the THS2.2 is not burnt. The low operating temperature of THS2.2 caused distinct shifts in the aerosol composition compared with 3R4F. This resulted in a reduction of more than 90% for the majority of the analyzed harmful and potentially harmful con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
288
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 292 publications
(336 citation statements)
references
References 58 publications
26
288
4
3
Order By: Relevance
“…Similar to the carbonyl compounds, the emissions of the volatile and semi-volatile compounds benzene, 1,3-butadiene, isoprene, styrene, and toluene were with a reduction of 97 to over 99% markedly lower when compared to combustible cigarettes (Table 1). The range of values found is again similar to the manufacturer’s data (Schaller et al 2016). To address consistency of nicotine and TPM release during the smoking procedure, the 12 puffs of the smoking protocol were divided into four intervals of three puffs each and analyzed separately.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Similar to the carbonyl compounds, the emissions of the volatile and semi-volatile compounds benzene, 1,3-butadiene, isoprene, styrene, and toluene were with a reduction of 97 to over 99% markedly lower when compared to combustible cigarettes (Table 1). The range of values found is again similar to the manufacturer’s data (Schaller et al 2016). To address consistency of nicotine and TPM release during the smoking procedure, the 12 puffs of the smoking protocol were divided into four intervals of three puffs each and analyzed separately.…”
supporting
confidence: 90%
“…Total particulate matter (TPM) was comparable to the manufacturer’s findings and higher than TPM from some combustible cigarettes. The yields of the carbonyl compounds formaldehyde, acetaldehyde, acrolein, and crotonaldehyde were, with a reduction of 80–96%, considerably lower when compared to combustible cigarettes (Table 1) and comparable to the published emissions observed by the manufacturer (Schaller et al 2016). Similar to the carbonyl compounds, the emissions of the volatile and semi-volatile compounds benzene, 1,3-butadiene, isoprene, styrene, and toluene were with a reduction of 97 to over 99% markedly lower when compared to combustible cigarettes (Table 1).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Pyrolysis of tobacco is an endothermic reaction which occurs at temperatures between 200°C and 600°C, during which the majority of volatile and semivolatile components of cigarette smoke are formed 21 22. Although the Philip Morris study indicated that the aerosol produced by iQOS devices reduce the amount of chemicals found on the Food and Drug Administration’s Harmful and Potentially Harmful Constituents list by limiting tobacco pyrolysis,5 our study, showing charring, in conjunction with a study by Auer et al , which confirmed the presence of volatile organic compounds, polycyclic aromatic hydrocarbons, carbon dioxide and nitric oxide,23 contradict the claim that tobacco pyrolysis is minimised in iQOS. Although iQOS operates at temperatures less than 350°C, this does not negate the formation of volatile and semivolatile harmful constituents of tobacco smoke, which tend to have boiling points that range from 70°C to 300°C 21 22…”
Section: Discussioncontrasting
confidence: 84%